Contagion - Soderbergh, Steven, 1963-; Burns, Scott Z.; Shamberg, Michael; Sher, Stacey; Jacobs, Gregory; Cotillard, Marion, 1975-; Damon, Matt.; Fishburne, Laurence, 1961-; Law, Jude, 1972-; Paltrow, Gwyneth, 1972-; Winslet, Kate.; Warner Bros. Pictures (1969- ); et al. (Burbank, Calif. : Warner Home Video, 2011)
A thriller centered on the threat posed by a deadly disease and an international team of doctors contracted by the CDC to deal with the outbreak.
Originally released as a motion picture in 2011.
Special feature: Contagion: how a virus changes the world.
Director of photography, Peter Andrews ; editor, Stephen Mirrione ; production designer, Howard Cummings ; music, Cliff Martinez.
Marion Cotillard, Matt Damon, Laurence Fishburne, Jude Law, Gwyneth Paltrow, Kate Winslet.
Rating: PG-13; for disturbing content and some language.
DVD; widescreen format; Dolby digital 5.1 surround, Dolby surround; NTSC region 1.
Keywords: Centers for Disease Control and Prevention (U.S.) -- Drama; Communicable diseases -- Drama; Feature films; Thrillers (Motion pictures); Films for the hearing impaired